Autophagy Supports Biomass Production and Nitrogen Use Efficiency at the Vegetative Stage in Rice. Issue 1 (18th March 2015) - Wada, Shinya; Hayashida, Yasukazu; Izumi, Masanori; Kurusu, Takamitsu; Hanamata, Shigeru; Kanno, Keiichi; Kojima, Soichi; Yamaya, Tomoyuki; Kuchitsu, Kazuyuki; Makino, Amane; Ishida, Hiroyuki
Abstract : Characterization of a rice mutant defective in autophagy highlights its importance in nitrogen remobilization from senescent leaves, biomass increase, and nitrogen use efficiency in the vegetative plant. Abstract: Much of the nitrogen in leaves is distributed to chloroplasts, mainly in photosynthetic proteins. During leaf senescence, chloroplastic proteins, including Rubisco, are rapidly degraded, and the released nitrogen is remobilized and reused in newly developing tissues. Autophagy facilitates the degradation of intracellular components for nutrient recycling in all eukaryotes, and recent studies have revealed critical roles for autophagy in Rubisco degradation and nitrogen remobilization into seeds in Arabidopsis ( Arabidopsis thaliana ). Here, we examined the function of autophagy in vegetative growth and nitrogen usage in a cereal plant, rice ( Oryza sativa ). An autophagy-disrupted rice mutant, Osatg7-1, showed reduced biomass production and nitrogen use efficiency compared with the wild type. While Osatg7-1 showed early visible leaf senescence, the nitrogen concentration remained high in the senescent leaves. 15 N pulse chase analysis revealed suppression of nitrogen remobilization during leaf senescence in Osatg7-1 . Accordingly, the reduction of nitrogen available for newly developing tissues in Osatg7-1 likely led its reduced leaf area and tillers. The limited leaf growth in Osatg7-1 decreased the photosynthetic capacity of the plant. Much of the nitrogen remaining in senescent leaves of Osatg7-1 was in soluble proteins, and the Rubisco concentration in senescing leaves of Osatg7-1 was about 2.5 times higher than in the wild type. Transmission electron micrographs showed a cytosolic fraction rich with organelles in senescent leaves of Osatg7-1 . Our results suggest that autophagy contributes to efficient nitrogen remobilization at the whole-plant level by facilitating protein degradation for nitrogen recycling in senescent leaves.